Optimalisasi Strategi Bisnis BUMDes "Sidomulyo Bahagia" Kecamatan Silo, Jember melalui Pendampingan Usaha Berbasis Business Model Canvas untuk Meningkatkan Kinerja dan Keberlanjutan - Mulyono, Resha Dwi Ayu Pangesti; Rosa, Dien Vidia; Karimah, Maulidya Nisa’ul; Soeprapto, Devina Elmira (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2025)
One of the prerequisites for a village to achieve self-reliance is authority and potential or assets. Building a Village-Owned Enterprise (BUMDes) is a crucial step towards realizing economic independence in the village. BUMDes aims to empower and enhance the productivity of rural communities by establishing business units within the community through management practices that align with current business models. A distinguishing indicator is the consistent preparation of business plan documents. One approach to creating a business plan is the Business Canvas Model (BMC), a tool that helps in understanding and identifying business models in a more practical way. The objectives and targets of this service activity are to improve the quality and quantity of business units at BUMDes Sidomulyo, enhance the capabilities of the human resources (HR) involved in managing BUMDes and the village community, increase village revenue (PAD) through scaling up BUMDes operations, and reduce the unemployment rate in the surrounding area. The outputs of this service activity include a module on the Business Canvas Model applied to BUMDes Sidomulyo, a scientific article in a national journal or conference proceeding, and a video of the activities uploaded to the YouTube channel of LP2M, University of Jember.